PENGARUH KERJASAMA TIM DAN KEPUASAN KERJA TERHADAP KINERJA PEGAWAI PADA KANTOR DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KABUPATEN TAPANULI TENGAH - Lase, Rut Monalisa; Hutagalung, Heriyawan; Ambarita, Rosmita (Jurnal Ekonomi Bisnis Digital, 2024)
This research aims to determine the effect of teamwork and job satisfaction on employee performance at the Population and Civil Registration Office of Central Tapanuli Regency. The type of research used in this research is a quantitative research method. The sample in this research were employees at the Population and Civil Registration Office of Central Tapanuli Regency with a questionnaire distributed to 78 (seventy eight) respondents. From the results of the t test in the research, it is known that the calculated t value of Teamwork is 5.086, greater than the t table of 1.665 (5.086 > 1.665), so the Teamwork variable (X1) has an effect on Employee Performance (Y) at the Population Service Office and Civil Registration of Central Tapanuli Regency, meaning Ho is rejected, Ha is accepted and Job Satisfaction is 3.523 > t table 1.665, then the Job Satisfaction variable (X2) has an effect on Employee Performance at the Population and Civil Registration Office of Central Tapanuli Regency, meaning Ho is rejected, Ha is accepted. Meanwhile, from the results of the F test, it is known that the calculated F value is 48.085 > F table 3.12 and the significance is 0.000 < 0.05, so the hypothesis states that Teamwork and Job Satisfaction have a significant effect together or simultaneously on Employee Performance at the Population and Civil Registration Office of Central Tapanuli Regency acceptable.